Transplantable Subcutaneous Hepatoma 22a Affects Functional Activity of Resident Tissue Macrophages in Periphery - Ekaterina P. Kisseleva; Andrei V. Krylov; Olga I. Stepanova; Victoria I. Lioudyno (International Journal of Cell Biology)
Tumors spontaneously develop central necroses due to inadequate blood supply. Recent data indicate that dead cells and their products are immunogenic to the host. We hypothesized that macrophage tumor-dependent reactions can be mediated differentially by factors released from live or dead tumor cells. In this study, functional activity of resident peritoneal macrophages was investigated in parallel with tumor morphology during the growth of syngeneic nonimmunogenic hepatoma 22a. Morphometrical analysis of tumor necroses, mitoses and leukocyte infiltration was performed in histological sections. We found that inflammatory potential of peritoneal macrophages in tumor-bearing mice significantly varied depending on the stage of tumor growth and exhibited two peaks of activation as assessed by nitroxide and superoxide anion production, 5′-nucleotidase activity and pinocytosis. Increased inflammatory reactions were not followed by the enhancement of angiogenic potential as assessed by Vascular Endothelial Growth Factor mRNA expression. Phases of macrophage activity corresponded to the stages of tumor growth characterized by high proliferative potential. The appearance and further development of necrotic tissue inside the tumor did not coincide with changes in macrophage behavior and therefore indirectly indicated that activation of macrophages was a reaction mostly to the signals produced by live tumor cells.